Gaya Bahasa Repetisi Dalam Tindak Tutur Asertif Pada Wacana Debat Keempat Calon Wakil Presiden Indonesia 2024 - Sunarni, Nani; Indrayani, Lia Maulia; Erlina, Erlina; Firmansyah, Eka Kurnia (Jurnal Sosioteknologi, 2025)
This study investigates the role of repetition as a linguistic strategy in assertive speech acts within the debate discourse of the fourth vice-presidential candidates leading up to the 2024 election. Specifically, it examines the thematic relationships between repetitive figures of speech and assertive speech acts used by the first, second, and third vice-presidential candidates, utilizing NVivo 12 Plus for data visualization. Adopting a qualitative descriptive method, the study identifies instances of repetition in assertive speech acts, categorizing them into two primary functions: "stating" (three instances) and "explaining" (three instances). A pragmatic analysis reveals that repetition occurs at both the word and phrase levels, primarily serving to reinforce emphasis and strengthen the speaker's stance in political discourse. Moreover, NVivo 12 Plus analysis illustrates a hierarchical structure linking figures of speech, assertive speech acts, and their communicative functions. These findings underscore the strategic role of repetition as a persuasive tool in political debates, demonstrating its effectiveness in reinforcing arguments and enhancing audience recall. The study offers practical insights into political communication strategies, particularly for speechwriters, debate analysts, and politicians seeking to optimize message clarity and impact.